Drivers of retention of the HIV workforce transitioned from PEPFAR support to the Uganda government payroll - Henry Zakumumpa; Joseph Rujumba; Marjorie Kyomuhendo; llyse Stempler; Woldekidan Amde (BMC, 2023)
Abstract Background Health worker (HW) retention in the public health sector in Uganda is an enduring health system constraint. Although previous studies have examined the retention of in-service HWs, there is little research focusing on donor-recruited HWs. The objective of this study was to explore drivers of retention of the HIV workforce transitioned from PEPFAR support to the Uganda government payroll between 2015 and 2017. Methods We conducted ten focus group discussions with HWs (n = 87) transitioned from PEPFAR support to the public sector payroll in 10 purposively selected districts across Uganda. In-depth interviews were conducted with national-level stakeholders (n = 17), district health and personnel officers (n = 15) and facility in-charges (n = 22). Data were analyzed by a hybrid approach of inductive and deductive thematic development based on the analytical framework by Schaefer and Moos regarding individual-level and organizational-context drivers. Results At the individual level, job security in the public sector was the most compelling driver of health worker retention. Community embeddedness of HWs in the study districts, opportunities for professional development and career growth and the ability to secure salary loans due to 'permanent and pensionable' terms of employment and the opportunity to work in 'home districts', where they could serve their 'kinsmen' were identified as enablers. HWs with prior private sector backgrounds perceived public facilities as offering more desirable challenging professional work. Organizational context enablers identified include perceptions that public facilities had relaxed supervision regimes and more flexible work environments. Work environment barriers to long-term retention include frequent stock-out of essential commodities, heavy workloads, low pay and scarcity of rental accommodation, particularly in rural Northern Uganda. Compared to mid-cadres (such as nurses and midwives), higher calibre cadres, such as physicians, pharmacists and laboratory technologists, expressed a higher affinity for seeking alternative employment in the private sector in the immediate future. Conclusions Overall, job security was the most compelling driver of retention in public service for the health workforce transitioned from PEPFAR support to the Uganda government payroll. Monetary and non-monetary policy strategies are needed to enhance the retention of upper cadre HWs, particularly physicians, pharmacists and laboratory technologists in rural districts of Uganda.